.69x+19=43

Simple and best practice solution for .69x+19=43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .69x+19=43 equation:


Simplifying
0.69x + 19 = 43

Reorder the terms:
19 + 0.69x = 43

Solving
19 + 0.69x = 43

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-19' to each side of the equation.
19 + -19 + 0.69x = 43 + -19

Combine like terms: 19 + -19 = 0
0 + 0.69x = 43 + -19
0.69x = 43 + -19

Combine like terms: 43 + -19 = 24
0.69x = 24

Divide each side by '0.69'.
x = 34.7826087

Simplifying
x = 34.7826087

See similar equations:

| y/4=5/13 | | 675x+125=3175 | | 3y^3-2y=x-3 | | 55x+850=123 | | y-1=2/3(x=9) | | x*10+12*8=196 | | 10=y+z | | x/2-=1 | | u/10=13/11 | | 5(2x+1)=-2(3x-5) | | 6y+9-5y=-3 | | b-11.33=3.833 | | x+2.4=6.8 | | (3x+2)+58=90 | | y=2.7x+10 | | 7(d-4)+3= | | x-2+37=4x | | 2.2+x=3.5 | | (2x-1)(3-x)=6 | | 20x^2-7x=3 | | 34-171/2y=-8 | | 7z-3(4-z)=5(2z)+12 | | 6/7x6/7x6/7 | | (3x-5)+(2x+5)=180 | | 3x-5=-10-2x | | 5(2x-1)=-2(3x-5) | | -20=2x(-2-3) | | 3x+5=x-2(modx) | | 4(4d-3)=8d-36 | | (10a)/(5a^5*5) | | 3x-6=-x-6 | | 4=H |

Equations solver categories